2018
DOI: 10.1186/s13011-018-0159-0
|View full text |Cite
|
Sign up to set email alerts
|

Financial hardship and drug use among men who have sex with men

Abstract: BackgroundLittle is known about the role of financial hardship as it relates to drug use, especially among men who have sex with men (MSM). As such, this study aimed to investigate potential associations between financial hardship status and drug use among MSM.MethodsWe conducted a cross-sectional survey of 580 MSM in Paris recruited using a popular geosocial-networking smartphone application (GSN apps). Descriptive analyses and multivariate analyses were performed. A modified Poisson model was used to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…In addition, our study also showed that prevalence of SDU and chemsex among GBMSM in Hong Kong was lower than that of Western Europe, Australia, the United States and mainland China [5,6,[10][11][12][13][14]. Similar to previous findings, SDU in the past year was associated with higher prevalence of anal intercourse with NRP and CAI with men.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, our study also showed that prevalence of SDU and chemsex among GBMSM in Hong Kong was lower than that of Western Europe, Australia, the United States and mainland China [5,6,[10][11][12][13][14]. Similar to previous findings, SDU in the past year was associated with higher prevalence of anal intercourse with NRP and CAI with men.…”
Section: Discussionsupporting
confidence: 87%
“…A high prevalence of SDU was reported among GBMSM in the United States (43%), Australia (54%), and Western Europe (18-54%) [5,6,[10][11][12][13]. The rates were slightly lower in Asia, ranged from 28% in mainland China, 18% in Thailand, 14% in Vietnam, to 7% in Malaysia [14].…”
Section: Introductionmentioning
confidence: 99%
“…The rate was higher than that of GBMSM in general in Hong Kong (27). Data on willingness to pay suggested that the current market rate for obtaining PrEP in Hong Kong (HK$8,000 per month) was not affordable for this group of GBMSM, as In addition, our study also showed that prevalence of SDU and chemsex among GBMSM in Hong Kong was lower than that of Western Europe, Australia, the United States and mainland China (5,6,(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 65%
“…Our results also suggested that increasing positive attitudes toward PrEP, creating subjective norm supporting PrEP use, and enhancing perceived behavioral control of using PrEP are potential useful strategies to promote PrEP, as these factors were significantly associated with willingness to use PrEP. In addition, our study also showed that prevalence of SDU and chemsex among GBMSM in Hong Kong was lower than that of Western Europe, Australia, the United States and mainland China (5,6,(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 51%